How critical thinking, multicultural education and teacher qualification affect anti-immigrant attitudes. Issue 1 (2nd January 2018) - Hjerm, Mikael; Johansson Sevä, Ingemar; Werner, Lena
Abstract: Previous studies identify a relationship between education and anti-immigrant attitudes. There is, however, uncertainty regarding the underlying explanations linking education to attitudes. In this article, we examine whether a relationship exists between exposure to teaching about critical thinking as well as multiculturalism (measured as religions/cultures as well as xenophobia/racism), and anti-immigrant attitudes among adolescents. In addition, we examine whether teacher qualification matters for attitudes. The analysis is based on survey data collected from high school students in Sweden. The results show an association between exposure to teaching about critical thinking as well as multiculturalism (both indicators) and anti-immigrant attitudes among students, i.e. higher exposure is related to lower levels of anti-immigrant attitudes. However, we find that teaching about xenophobia/ racism affects attitudes, but not when simultaneously controlling for teaching about critical thinking and religions/cultures. In terms of teacher qualification, we find that students in schools with a high proportion of certified teachers tend to have lower levels of anti-immigrant attitudes.